2000
DOI: 10.1088/0953-4075/33/18/315
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of scandium and vanadium K-shell ionization cross sections by electron impact

Abstract: Electron impact Sc and V K-shell ionization cross sections have been measured for the first time in the incident energy region from near threshold to 45 keV. Thin targets with thick substrates are used in the experiments. The influence of the substrate on measured data has been corrected by a method based upon an electron transport calculation. For Sc and V elements, the experimental data are compared with some empirical formulae and theoretical results. It is found that the experimental data for Sc and V and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
(43 reference statements)
5
20
0
Order By: Relevance
“…cross section curves are summations over all the fine-structure transitions from the V 0 ground level. The available experimental data [35,36] agree well with our model (RDW + Extrapol.) within their respective error bars.…”
Section: Calculationssupporting
confidence: 84%
See 2 more Smart Citations
“…cross section curves are summations over all the fine-structure transitions from the V 0 ground level. The available experimental data [35,36] agree well with our model (RDW + Extrapol.) within their respective error bars.…”
Section: Calculationssupporting
confidence: 84%
“…1, our calculated K-shell EII cross sections in V 0 are compared to the experimental data compiled by Liu et al [35], the measurements of An et al [36], the empirical XCVTS formula of Haque et al [34], the combination of distorted-wave-Born and plane-wave-Born approximations (DWBA + PWBA) of Bote et al [33], the MRBEB model of Guerra et al [30] and this latter model corrected for the density effect as suggested by Davies et al [1] (MRBEB + Density Effects). Our RDW + Extrapol.…”
Section: Calculationsmentioning
confidence: 86%
See 1 more Smart Citation
“…• Scandium: The experimental results by An et al [2] are not in agreement with any of the theories presented here, so new experimental data are required to better understand this case.…”
Section: K-shell Ionizationmentioning
confidence: 65%
“…The experimental data are taken from Shah et al 33 for H; Nagy et al 34, Rejoub et al 35, Schram et al 36 and Shah et al 37 for He; Tawara et al 38 for N, O and Ne; Gulpe and Mehlhorn 39, 40 for N, O and Ne; Platten et al 41 for O, Ne, Si and Ar; Kamiya et al 42 for Al; Ishii et al 43 for Al, Si, Ca, Zn, Se, Y, Mo, Pd, In, Sn, Ba, Au, Pb, Bi and U; McDonald and Spicer 44 for Al; Hoffmann et al 45, 46 for Al, Si, Ar, Ca, Cr, Mn, Ni, Cu, Ge, Y, Ag, Sn, Au, Pb and Bi; Hink and Ziegler 47 for Al; Quarles and Semaan 48 for Ar; Shevelko et al 49 for K, Ca, Rb and Sr; Jessenberger and Hink 50 for Ti and Ni; He et al 51 for Ti, Cr and Mo; An et al 52 for V and 53 for Co; Scholz et al 54 for V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Se, Rb, Sr, In, Sn, Ba, Pb and Bi; Luo et al 55 for Cr and Mo, and 56 for Mn; Llovet et al 56 for Mn and Fe; Shima et al 58 for Mn and Cu; Shima 59 for Cu; Pockman et al 60 for Ni; Genz et al 61 Ni, Cu and Ag; Seif al Naser et al 62 for Ni, Y, Ag, Ta, Au and Pb; Middleman et al 63 for Cu, Sr, Mo, In, Ta, Au and Bi; Hubner et al 64 for Cu; Tang et al 65 for Zn; Zhou et al 66 for Ga and Ge; Berenyi et al 69 for Se; Kiss et al 68 for Se; Berkner et al 69 for Pd and Au; Ricz et al 70 for Pd, Ag, In and Sn; Rester and Dance 71 for Ag, Sn and Au; Schlenk et al 72 for Ag; Davis et al 73 for Ag and Au.…”
Section: Resultsmentioning
confidence: 99%